211k views
5 votes
For the function find f-1(x)

For the function find f-1(x)-example-1

1 Answer

6 votes

as you already know, to get the inverse of any expression we start off by doing a quick switcheroo on the variables and then solve for "y".


\stackrel{f(x)}{y}=\sqrt[3]{x^5-3}\implies \stackrel{\textit{quik switcheroo}}{x = \sqrt[3]{y^5-3}}\implies \stackrel{\textit{cubing both sides}}{x^3=y^5-3} \\\\\\ x^3+3=y^5\implies \sqrt[5]{x^3+3}=\stackrel{f^(-1)(x)}{y}

User BZKN
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.